2020
DOI: 10.33793/acperpro.03.01.58
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laser Beam Wobbling Mode on Weld Bead Geometry of Tailor Welded Blanks

Abstract: As a higher weight leads to increased fuel consumption for the automobile industry, the body in white must be lighter to compensate for the weight of additional components. Therefore, tailored blanks are used, which reinforce the body in white only in areas where a higher strength or stiffness is necessary. The applicability of laser welding processes with its numerous advantages, such as low heat input and production efficiency, is often limited when joining imperfect edges steel sheets due to small gap bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As far back as the 1990s, Rubben et al 20 showed the bene ts of using a oscillating laser in the production of tailored blanks. Kuryntsev & Gilmutdinov 21 and Yuce 22 both demonstrated that laser oscillation can heal defects formed at the rst welding pass and bridge larger gaps, which are essential to applications with imperfect faying interfaces. Hao et al 23,24 tested a wide range of oscillation frequencies from 20 Hz to 1000 Hz on dissimilar steel systems to reveal the melt pool shape and melt track topology.…”
Section: Introductionmentioning
confidence: 99%
“…As far back as the 1990s, Rubben et al 20 showed the bene ts of using a oscillating laser in the production of tailored blanks. Kuryntsev & Gilmutdinov 21 and Yuce 22 both demonstrated that laser oscillation can heal defects formed at the rst welding pass and bridge larger gaps, which are essential to applications with imperfect faying interfaces. Hao et al 23,24 tested a wide range of oscillation frequencies from 20 Hz to 1000 Hz on dissimilar steel systems to reveal the melt pool shape and melt track topology.…”
Section: Introductionmentioning
confidence: 99%
“…As far back as the 1990s, Rubben et al 20 showed the benefits of using an oscillating laser in the production of tailored blanks. Kuryntsev & Gilmutdinov 21 and Yuce 22 both demonstrated that laser oscillation can heal defects formed at the first welding pass and bridge larger gaps, which are essential to applications with imperfect faying interfaces. Hao et al 23,24 tested a wide range of oscillation frequencies from 20 to 1000 Hz on dissimilar steel systems to reveal the melt pool shape and melt track topology.…”
mentioning
confidence: 99%